Randomized comparison of pazopanib and doxorubicin as first-line treatment in patients with metastatic soft tissue sarcoma age 60 years or older: results of a German intergroup study - Grünwald, Viktor; Karch, Annika; Schuler, Markus; Schöffski, Patrick; Kopp, Hans-Georg; Bauer, Sebastian; Kasper, Bernd; Lindner, Lars H.; Chemnitz, Jens-Marcus; Crysandt, Martina; Stein, Alexander; Steffen, Björn; et al. (Journal of clinical oncology, 2020)
Purpose: Doxorubicin is a standard of care in patients with advanced, inoperable soft tissue sarcoma (STS). We tested whether pazopanib has efficacy comparable to that of doxorubicin in elderly patients with STS and offers superior tolerability for hematologic toxicity. Patients and methods: Patients age 60 years or older without previous systemic treatment for progressive advanced or metastatic STS who had Eastern Cooperative Oncology Group performance status of 0 to 2 and adequate organ function were included. Treatment consisted of pazopanib 800 mg once per day or doxorubicin 75 mg/m2 once every 3 weeks (≤ 6 cycles) after being randomly assigned in a 2:1 ratio. Noninferiority was assumed for progression-free survival (PFS), if the upper limit of the 95% CI for the hazard ratio (HR) was less than 1.8. Neutropenia and febrile neutropenia were key secondary end points. The European Organisation for Research and Treatment of Cancer (30-item) Quality of Life Questionnaire and geriatric assessment were used to measure patient-reported outcomes. Cox regression analysis and Kaplan-Meier curves were used for analysis. Results: Pazopanib and doxorubicin were given to 81 and 39 patients, respectively. The median age was 71 years (range, 60-88 years). PFS was noninferior (HR, 1.00; 95% CI, 0.65 to 1.53) and the incidence of grade 4 neutropenia and febrile neutropenia favored pazopanib. Objective response rates for pazopanib and doxorubicin were 12.3% and 15.4%, respectively. Overall survival did not differ significantly between arms (HR, 1.08; 95% CI, 0.68 to 1.72; P = .735). Geriatric assessment revealed 2 or more comorbidities in 15.8% of the patients and impairment of activities of daily living in 28.3% of patients. Conclusion: Pazopanib was noninferior to doxorubicin, rendering pazopanib a putative therapeutic option in the first-line treatment of STS in patients age 60 years or older. The distinct adverse event profile may be used to counsel patients and tailor therapy to individual needs.